China's country image in the eyes of international students from central Asian countries - Zhao, Xueyan; You, Xuqun; Lin, Shanyan (Frontiers in Psychology, 2022)
The present study investigated the conceptualization and measurement of China’ country image (CI) and its effects on the economic image, product image, national image and residence intention of individuals in central Asian countries. A total of 297 international students from central Asia were recruited to complete an online survey. The confirmatory factor analysis showed that CI was a multidimensional construct consisting of a cognitive component and an affective component. China’ CI before and after coming to China was compared by using a repeated-measures ANOVA and paired t tests, and the results suggested a significant difference in government image and international image but no significant difference in social image. The regression analysis showed that CI significantly predicted the economic image, product image, national image and individual’s residence intention. This study may contribute to developing policies to improve the country image.